Con Safos Interview Parts 10A-12A
Interview with members of Con Safos Magazine. Interview done by Founding Director and Chief Curator of The Latino Museum of History, Art, and Culture, Denise Lugo. Date of interview approx. late 1990s. Videos made digital in 2010.